Prisoners of the castle: an epic story of survival and escape from Colditz, the Nazis´ fortress prison - Macintyre, Ben (Crown, 2022)
Prologue: Franz Josef -- The Originals -- Le Ray's Run -- The Bad Boys' Camp -- Goon-Baiting -- Ballet Nonsense -- Le Métro -- Clutty of MI9 -- Seeking for a Path -- Dogsbody -- The Prominente Club -- Shabash -- The Dentist Spies -- Madness -- The Sparrows -- The Red Fox -- The Rhine Maiden -- Besieged -- Endgame.